PERTANGGUNGJAWABAN TERHADAP KORBAN JUGUN IANFU DI INDONESIA SEBAGAI WUJUD REALISASI BUDAYA MALU BANGSA JEPANG - Samuel H. M. Manik (Jurnal Pustaka Nusantara dan Budaya, 2013)
Shame is a psychological reaction that occurs due to the criticism of others, or comes about when other people laugh. Means prioritizing assessment shame society in general. Shame culture is one of the most influential culture to the Japanese people. Responsibility towards victim of Jugun Ianfu is a kind of shame culture of Japan. In writing this journal, the author uses library research and descriptive analyzes were done by describing the data that author got from any references and then analyze it.In addition, the author also uses historycal and sociological theory in this study. The purpose of this research was to descript culture of shame of Japanese people in the context of responsibility towards the victim of Jugun Ianfu in Indonesia. The advantage of this research is to increase the understanding of a shame culture as the characteristic of Japanese that applied in the responsibility towards the victim of Jugun Ianfu. The result of this research shows that there is a realization of culture that shown by Japan towards the world in the form of apologize and compensation towards the victim of Jugun Ianfu, especially in Indonesia.